Factors That Influence The Interest In Buying Local Brand Thanksinsomnia Among Youth In Surabaya - Ahmad Iqbal Taufiqul Hakim; Dwi Widi Hariyanto; Endang Muryani (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
This study aims to determine whether product quality and brand image affect consumer buying interest and analyze the effect of product quality and brand image on buying interest in the Thanksinsomnia brand in Surabaya. The population in this study were consumers of the Thanksinsomnia brand in Surabaya. The sample was taken as many as 107 respondents using the Non-Probability Sampling technique with the Accidental Sampling approach, namely the technique of determining the sample based on chance, that is, anyone who happens to meet with the researcher can be used as a sample if deemed suitable.Based on the research results, the results of the regression analysis are as follows Y = 3.801 + 0.214 X1 + 0.261 X2. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. In the classical assumption test, the regression model is multicollinearity free, does not occur heteroscedasticity, and is normally distributed. The individual order of each variable that has the most influence is product quality of 0.379, then brand image with a regression coefficient of 0.262. Thanksinsomnia brand needs to maintain the elements that have been rated well by customers and need to improve the things that are still lacking.